ANALISIS KARIOTIPE PISANG MAULI - Mailina Yulianty (Universitas Lambung Mangkurat, 2006)
Pisang Mauli is a famous and delicious banana that grows plenty throughout Kalimantan Selatan. The banana quality should be improved to that of quality commercial fruit in order to allow the fruit accepted in the global market. The efforts of improvement may include genetic manipulation which requires the cytogenetic information of the banana. However, to the knowledge of authors, the cytogenetic information of pisang Mauli of Kalimantan Selatan is not available. Therefore, the objective of this research was to investigate the number and karyotype of pisang Mauli chromosomes, and its original genomes. The chromosomes were stained with 2 % aceto-orcein by squash method. Mitotic cells of pisang Mauli have 22 chromosomes which consist of 7 pair metacentric and 4 pair submetacentric chromosomes. Chromosome number 10 has a satellite at the tip of its short arm. Cytogenetic and morphological data of Pisang Mauli suggest that it belongs to AA genome group and subgroup pisang Mas.